MODEL PENGELOLAAN KELAS DALAM MENDUKUNG PEMBELAJARAN EFEKTIF ABAD KE-21 DI SEKOLAH DASAR - Sahla Adhitia, Munifa; Aulya Fathinah, Nadiah; Novita Sari, Nadiya; Khoirunisa, Nabila; Rangkuti, Nabilah; Iskandar, Sofyan (Penerbit Lafadz Jaya, 2025)
This research examines effective classroom management models supporting 21st-century learning in primary schools, particularly within the Merdeka Curriculum implementation context. The study addresses the significant gap between learning theories and classroom practice, compounded by infrastructure limitations. Using a qualitative descriptive approach, the research involved observations and interviews with five students, five teachers, one principal, and five community members from SDN Dawuan 1 through purposive sampling. Data analysis employed thematic analysis following Braun and Clarke's methodology, with triangulation and member checking for credibility. Results demonstrate that SDN Dawuan 1 successfully transformed teacher-centered learning toward student-centered approaches, implementing diverse and flexible classroom management strategies. Teachers developed varied instructional methods including group discussions, project-based learning, and video utilization to enhance student engagement. Despite lacking physical facilities, teachers creatively integrated simple technologies like projectors and laptops as substitutes. Significantly, the study found that teacher pedagogical competence, visionary school leadership, and supportive learning environments are more determinant factors in achieving effective learning than physical infrastructure alone. The research concludes that comprehensive classroom management effectively supports 21st-century skill development through collaborative activities, problem-solving, and creative exploration, establishing that synergy among teacher competence, school policy, and learning environment quality are critical for educational success.